MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Dian Oktaviani (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical communication is something that is needed by students in learning mathematics. This study was a quasi-experiment with the aim of to know mathematical communication students who studied with problem based learning models. This research was conducted on class VIII. Sampling was done by using simple random sampling. The instrument that was used to collect the Junior High School, data in this research was final test in essay form test which consisted of 7 questions, where each question contains indicators of mathematical communication. The results show that the mathematical communication of student in experiment class students had increased for each indicator. Based on the results of data analysis, by doing t test at significant level of 0,05, it is obtains P-Value = 0,000. Because of the P-Value < 0.05, then H0 is rejected, so that mathematical communication of students who learn the problem learning model are better than students who learn with conventional learning.Keyword - Mathematics Communication, Problem Based Learning.